2019
DOI: 10.1016/j.cell.2018.11.031
|View full text |Cite
|
Sign up to set email alerts
|

A Small Helical Bundle Prepares Primer Synthesis by Binding Two Nucleotides that Enhance Sequence-Specific Recognition of the DNA Template

Abstract: Graphical Abstract Highlights d Liquid-and solid-state NMR structure of a primase HBD bound to DNA and two ATPs d ATP binding triggers the sequence-specific DNA recognition of the primase HBD d In binding nucleotides and template, the HBD prepares dinucleotide synthesis d This preparatory role of the HBD is conserved in archaeoeukaryotic primases

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(71 citation statements)
references
References 51 publications
7
62
0
Order By: Relevance
“…To be sure, replication initiation involves a multiprotein complex, with, beside DnaA, helicase PriA as another ATPdependent factor that could act as a further discriminating MxD or possibly as a mechanical transducer (Windgassen et al, 2018). DNA primase, that starts replication, might even combine recognition of the target initiation site with formation of a first dinucleotide primer made from the two ATP molecules used in the process, an economical way to make use of ATP in the process (Boudet et al, 2019).…”
Section: Other Processes Working Out Specific Features Of Nucleic Acidsmentioning
confidence: 99%
“…To be sure, replication initiation involves a multiprotein complex, with, beside DnaA, helicase PriA as another ATPdependent factor that could act as a further discriminating MxD or possibly as a mechanical transducer (Windgassen et al, 2018). DNA primase, that starts replication, might even combine recognition of the target initiation site with formation of a first dinucleotide primer made from the two ATP molecules used in the process, an economical way to make use of ATP in the process (Boudet et al, 2019).…”
Section: Other Processes Working Out Specific Features Of Nucleic Acidsmentioning
confidence: 99%
“…Sample preparation by sedimentation allowed for the investigation of proteins that are difficult (or even impossible) to crystallize. Theoretically, the molecular mass of the protein determines the success of sedimentation, and proteins, such as the RNA polymerase subunits Rpo4/7 * (the * indicates that the Rpo7 unit is uniformly 13 C/ 15 N labeled) with a molecular weight of 34 kDa (Torosyan et al, 2019), the pRN1 primase with 40 kDa (Boudet et al, 2019), the neonatal Fc receptor with 40 kDa (Stöppler et al, 2018) as well as the human superoxide dismutase with 32 kDa (Fragai et al, 2013), the bacterial helicase DnaB with 708 kDa (Gardiennet et al, 2012), the iron-storage protein ferritin with 480 kDa (Bertini et al, 2012), a variety of supramolecular assemblies (Lecoq et al, 2018;Gauto et al, 2019), and PEGylated proteins (Ravera et al, 2016), were shown to form sediments suitable for solid-state NMR. This is for some of these systems probably a consequence of oligomerization that has been induced by the high protein concentrations (Bertini et al, 2013;Fragai et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we describe our experimental observations regarding the stability of four sedimented samples from different protein systems: (i) the bacterial helicase DnaB from Helicobacter pylori in a complex with ADP:AlF 4 − and DNA (Wiegand et al, 2019), (ii) the archaeal pRN1 primase from Sulfolobus islandicus in a complex with DNA and ATP (Boudet et al, 2019), (iii) the membrane protein BmrA, an ABC transporter from Bacillus subtilis (Lacabanne et al, 2019b), and (iv) the two RNA polymerase subunits Rpo4/7 * from Methanocaldococcus jannaschii. We use 2D DARR spectra and 31 P cross polarization (CP) MAS experiments to assess the long-term stability of these sedimented protein samples.…”
Section: Introductionmentioning
confidence: 99%
“…A nuclear magnetic resonance study on the primase part of primase-polymerase ORF904 from archaeal plasmid pRN1 showed the helix bundle domain of ORF904 bound to template DNA and two ATP molecules, suggesting that this structure represents an early step of the catalytic cycle before the template DNA and the two nucleotides are transferred to the catalytic domain for dinucleotide formation (17).…”
Section: Introductionmentioning
confidence: 99%